PENGOBATAN TRADISIONAL SUKU SASAK BERBASIS ILMIAH DI KABUPATEN LOMBOK BARAT - Husnul Jannah; Ridwan Ridwan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2013)
This study was conducted with the aim to inventory the name, way of making, and how the use of medicinal plants that are traditionally used by the people of West Lombok Regency from generation to generation. This research is descriptive research using qualitative approach with stages include observation of research object, direct interview with respondent, and documentation of name, way of making and use of medicinal plants. The results of this study indicate that in general the community Sasak West Lombok regency uses about 76 types of plants to treat various diseases, but of all types of plants there are some plants that are not used in general throughout the district of West Lombok but specifically used in certain places only.